Drought-fuelled overnight burning propels large fires in North America - Balch, Jennifer K.; Mahood, Adam L. (Nature (London), 2024)
Burning events that occur at night have been revealed as a driver of large wildfires. Prolonged drought conditions are to blame, making it easier for fires to spread at night when they would ordinarily slow or extinguish completely. Analysis of large wildfires indicates key role of overnight burning.